2014
DOI: 10.1111/jvp.12098
|View full text |Cite
|
Sign up to set email alerts
|

Preliminary pharmacokinetics of morphine and its major metabolites following intravenous administration of four doses to horses

Abstract: The objective of the current study was to describe the pharmacokinetics of morphine and its metabolites following intravenous administration to the horse. A total of eight horses (two per dose group) received a single intravenous dose of 0.05, 0.1, 0.2, or 0.5 mg/kg morphine. Blood samples were collected up to 72 h postdrug administration, analyzed using LC-MS/MS and pharmacokinetic parameters determined. Behavior, step counts, and gastrointestinal activity were also assessed. The beta and gamma half-life for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
51
1
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 34 publications
(63 citation statements)
references
References 22 publications
10
51
1
1
Order By: Relevance
“…[13] Although the biotransformation of morphine has not been well studied in the horse, it has recently been reported that morphine-3-glucuronide is the major phase II metabolite in plasma with morphine-6-glucuronide being a minor metabolite. This finding is consistent with the in vivo results reported recently by Knych et al [14] In addition, two more glucuronide metabolites of morphine were observed, namely, desmethylmorphine glucuronide and hydroxymorphine glucuronide as derived from their accurate mass and product-ion spectra. This could be supported by the fact that when morphine was incubated with homogenized liver in the presence of PAPS, no morphine sulfate was detected.…”
Section: Morphinesupporting
confidence: 93%
“…[13] Although the biotransformation of morphine has not been well studied in the horse, it has recently been reported that morphine-3-glucuronide is the major phase II metabolite in plasma with morphine-6-glucuronide being a minor metabolite. This finding is consistent with the in vivo results reported recently by Knych et al [14] In addition, two more glucuronide metabolites of morphine were observed, namely, desmethylmorphine glucuronide and hydroxymorphine glucuronide as derived from their accurate mass and product-ion spectra. This could be supported by the fact that when morphine was incubated with homogenized liver in the presence of PAPS, no morphine sulfate was detected.…”
Section: Morphinesupporting
confidence: 93%
“…The primary goal of the current study was to confirm and extend current knowledge regarding the metabolism, pharmacokinetics, and selected pharmacodynamics of morphine in healthy horses. A preliminary report was published previously, whereby the metabolism and pharmacokinetics of morphine when administered at 4 different doses (0.05, 0.1, 0.2, and 0.5 mg/kg) were described; however, the study size was small ( n = 2/dose group; Knych et al., ).…”
Section: Discussionmentioning
confidence: 99%
“…While the pharmacokinetics of morphine in the horse has been described previously (Combie, Nugent, & Tobin, ; Knych, Steffey, & McKemie, ), to the best of the authors’ knowledge, there is only a single study describing the metabolism of morphine in horses (Knych et al., ). Knych et al.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations